Makey mano - Ruslan, Muhammad Nazreen (Universiti Teknologi MARA, Perak, 2022)
Makey Mano was created to increase the visitors and reach over one millions visitors in Kelantan. However, Makey Mano also helping and sponsor the restaurants around the states to add their profit.